Burning issues in the prevention of heart failure - J. A. Ker; K. Outhoff (South African Family Practice)
Chronic heart failure is common, debilitating, and often the culmination of pervasive cardiovascular insults that systematically undermine the heart’s circulatory capacity and invoke counterproductive neuro-hormonal compensatory changes. Prevention of chronic heart failure therefore requires minimising the impact of traditional cardiovascular risk factors with incisive treatment of hypertension and type II Diabetes Mellitus (T2DM) and prompt lifestyle interventions for smoking, lack of exercise, obesity and hypercholesterolemia. This review is narrative, with selected emphasis on major studies, rather than structured on a specific clinical question, and should be read as such.